Rasio Efektivitas Dan Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah : (Studi Kasus Kota Madiun Tahun 2018-2022) - Widodo, Wahyu; Widodo, Nova Maulud; Prihadyatama, Ardila (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The Covid-19 pandemic in 2018 – 2022 will cause a decrease and increase in regional tax revenues, resulting in potential fluctuations in the level of effectiveness and tax contribution of a region. This research aims to determine the level of effectiveness and contribution of taxes in conditions before the pandemic, during the pandemic and after the pandemic. This research uses original regional income data and the realization of Madiun City regional taxes obtained directly from the Madiun City Revenue Agency. The data collection method is secondary data observation, using quantitative data so that researchers can make an analysis of the effectiveness and contribution of local taxes to Madiun City's local revenue. According to the research results, it can be seen that the effectiveness level of Madiun City is in the very effective category because the average value of effectiveness exceeds 100%, namely 111.67%. Madiun City's regional tax contribution is in the quite good category because it only gets an average value of 36.54% and this means that the majority of Madiun City's original regional income does not come from regional taxes but from other legitimate income such as asset sales and investments